Johannes’ Åbenbaring kap. 13 Overvejelser over tekstens aktualitet1 - Hallbäck, Geert (Dansk Teologisk Tidsskrift, 2012)
The apocalyptic beasts in Revelation chap. 13 have been identifi ed with a variety of historical persons. Such interpretive practice reveals a sort of hermeneutical narcissism. Before considering the contemporary relevance one has to consider the historical context. Chap. 12 introduces the mythological explanation of God’s will to destroy the whole world as revealed in the fi rst part of the book. The Dragon (Satan) is expelled from heaven, but reigns now on earth; therefore the earth has to be destroyed and Satan to be conquered once again. In chap. 13 two apocalyptic beasts are revealed, one from the sea and one from the land. They are fantastic representations of the Roman Empire and of the local supporters that worship the emperor. In this way the text is bound to its historical context. To ponder the contemporary relevance of the text we need to recognize its ‘productive malaise’. I suggest fi nding this malaise in the revelation of an ongoing competition between political power and religious faith, and I point to two low-key examples in contemporary Danish society: The decision of the Danish Parliament to impose homosexual weddings on the Danish Church, and the discussion of abandoning certain church holidays for economic reasons.